Um estudo sobre os sentidos do trabalho na Uberização em São José dos Campos - Barleta, Márcia Christina Ferreira (2020)
With the transformations that occurred in the work in the 21st century, new perceptions about its senses and meanings emerge. Around these aspects, arises the question that reveals the problem of this research: Which factors are considered relevant in the perception of transportation application drivers of São José dos Campos, regarding the senses and meanings of work in the contemporary context? The research main objective was to understand transportation applications drivers’ perception of São José dos Campos about the meanings of work and the relevant factors of this phenomenon. In order to make this study possible, it was chose to combine two data production instruments – the application of a survey questionnaire with the achievement of 106 samples and the application of semi-structured interviews to six application drivers of São José dos Campos (São Paulo). The analysis of these data is the exploratory descriptive and it was built considering the quantitative data of the questionnaire and qualitative performed with the statements of respondents to understand the meanings of communication. Factors that make the most sense in the perception of drivers of transportation applications were identified: social utility, autonomy and convenient working hours. The factors considered as average were: possibility of having good interpersonal relationships and opportunity for new learnings. In addition, the factors pointed out as more unsatisfactory were: safety in terms of physical integrity, theft risks and low remuneration. Therefore, there is some ambiguity in the work through applications. Satisfying factors that bring sense and meaning to the work combine with low satisfaction ratings with platform remuneration systems, the customer evaluation system and transportation application companies. When relating the questionnaire’s results with the interviews’ results, it is possible to highlight: the importance of possibility to have a job; the association of autonomy with time flexibility; the remuneration associated with the amount of hours worked; and the opportunity for new learnings through good interpersonal relationships